2018
DOI: 10.1002/adfm.201805279
|View full text |Cite
|
Sign up to set email alerts
|

Field‐Effect Transistors on Photonic Cellulose Nanocrystal Solid Electrolyte for Circular Polarized Light Sensing

Abstract: The integration of bioinspired chiral cellulose nanocrystal (CNC) films into transistor devices with distinct sensing properties for left‐ and right‐handed circular polarized light (LCPL and RCPL, respectively) is reported. The CNC films with a left‐handed internal long‐range order are infiltrated with sodium ions to yield solid‐state electrolytes with photonic properties capable of LCPL reflection and RCPL transmission. They are employed as gate dielectrics in sputtered amorphous indium–gallium–zinc oxide (a‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…[11,16] When using responsive polymers or stretchable rubbers, the PBG of such CNC composite materials can be changed by external triggers, endowing these systems with responses that qualify for sensor applications. [17] While these passive photonic systems have reached relevant functional material levels, until today, there are no examples, where the self-assembly of CNC has been exploited to sculpt the active emission of light in photonic devices. Such an approach toward active optical resonators and lasers would push the functionality of CNC-based materials to a new level and combine it with interesting multifunctionality benefits of CNCs such as The transition toward future sustainable societies largely depends on disruptive innovations in biobased materials to substitute nonsustainable advanced functional materials.…”
Section: Doi: 101002/adma202002332mentioning
confidence: 99%
“…[11,16] When using responsive polymers or stretchable rubbers, the PBG of such CNC composite materials can be changed by external triggers, endowing these systems with responses that qualify for sensor applications. [17] While these passive photonic systems have reached relevant functional material levels, until today, there are no examples, where the self-assembly of CNC has been exploited to sculpt the active emission of light in photonic devices. Such an approach toward active optical resonators and lasers would push the functionality of CNC-based materials to a new level and combine it with interesting multifunctionality benefits of CNCs such as The transition toward future sustainable societies largely depends on disruptive innovations in biobased materials to substitute nonsustainable advanced functional materials.…”
Section: Doi: 101002/adma202002332mentioning
confidence: 99%
“…Taking advantage of this property, cellulose nanocrystals also are suitable candidates for CPL detection. In 2018, Pereira et al ( Grey et al, 2018 ) used chiral cellulose nanocrystal films as gate dielectrics and amorphous indium-gallium-zinc-oxide (a-IGZO) as the semiconductor layer to fabricate a bottom-gate architecture transistor, as shown in Figure 8A . Experimental results revealed that around 35% LCPL was reflected by the CNC:Na layer, while around 90% of the RCPL was transmitted which reached the a-IGZO layer.…”
Section: Exploration Of Circularly Polarized Light Detectors With Excellent Performancementioning
confidence: 99%
“…Such a complicated device configuration does not meet the demands of miniaturization trends, which is also incompatible with the emerging wearable technology. Recently, polarization‐sensitive semiconductor CPL photodetectors have arisen . The semiconductor CPL photodetectors can directly distinguish between left‐handed (LCP) and right‐handed CPL (RCP) via electrical signals, which exhibit great promise to overcome the shortcomings.…”
Section: Introductionmentioning
confidence: 99%